An Application of a Poisson Distribution Series on Certain Analytic Functions. (18th February 2014) - Porwal, Saurabh
Abstract : The purpose of the present paper is to introduce a Poisson distribution series and obtain necessary and sufficient conditions for this series belonging to the classesT ( λ, α ) andC ( λ, α ) . We also consider an integral operator related to this series.